KULTUR ANTERA ANTHURIUM: PENGARUH SUKROSA DAN GLUKOSA TERHADAP KEBERHASILAN INDUKSI PEMBENTUKAN KALUS DAN REGENERASINYA - Budi Winarto; N.A. Mattjik; A. Purwito; B. Marwoto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
Effect of sucrose and glucose on callus induction and formation, growth and its regeneration was studied in tissue culture laboratory of Indonesian Ornamental Crops Research Institution from January to November 2009. Objective of this study was to know different combination-concentration of sucrose and glucose on callus induction and formation, growth and its regeneration in anther culture of anthurium. Anthers harvested from spadix with 50% of their pistil in optimal receptive, callus derived from them, Winarto and Rachmawati medium containing 1.5 mg/l TDZ, 0.75 mg/l BAP and 0.02 mg/l NAA were used in the study. Sucrose concentrations were (1) 20 g/l, (2) 40 g/l, (3) 60 g/l dan (4) 80 g/l. While glucose concentrations were (1) 0 g/l, (2) 10 g/l, (3) 30 g/l dan (4) 60 g/l. Variation of the concentrations was applied in callus induction, growth and its regeneration studies. Factorial experiment was arranged by completely randomized design with four replications. Results of this research indicate that existence of sucrose in Winarto and Rachmawati medium gave high effect on successful in antera culture of anthurium and its callus regeneration compared to glucose. Increasing sucrose concentration from 30 g/l to 60 g/l had high impact in callus formation, growth and its regeneration. Sucrose of 60g/l in combination with 30 g/l glucose was the most suitable combination treatment for callus induction and formation with potential growth of antera up to 92%, 67% antera regeneration and 4.0 calluses formed per replication. The sucrose concentration was also tobe the best concentration callus growth and its regeneration with 332 mm3 per callus and 3.2 shoots per explant.